Natryptite dental glass ceramic, chemically strengthened Natryptite dental glass ceramic, and preparation method and application of chemically strengthened Natryptite dental glass ceramic

By developing sodium galvanized dental microcrystalline glass, using specific group distribution ratios and preparation processes, the shortcomings of existing dental restorative materials in terms of mechanical properties are solved, and the effects of high flexural strength, toughness and hardness are achieved, and it is suitable for high-performance dental materials.

CN119528441APending Publication Date: 2025-02-28深圳市昊迦科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411701332.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing dental restoration materials have shortcomings in mechanical properties, especially in terms of flexural strength and toughness, which are difficult to meet high performance needs.

Method used

A sodium galactite dental microcrystalline glass was developed to improve its mechanical properties through specific composition distribution ratios and preparation processes, including SiO2, Al2O3, Na2O, Li2O and other components, and to improve its mechanical properties through nucleation and crystallization treatment.

Benefits of technology

It has achieved high bending strength, toughness and hardness of sodium galvanized dental microcrystalline glass, and has excellent mechanical properties, chemical stability and biocompatibility, and is suitable for high-performance dental materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528441A_ABST
    Figure CN119528441A_ABST
Patent Text Reader

Abstract

The invention discloses a soda nepheline dental glass ceramic, a chemically strengthened soda nepheline dental glass ceramic and a preparation method and application thereof, and relates to the field of glass ceramics, the soda nepheline dental glass ceramic comprises the following components by molar percentage: 40-55% of SiO2, 15-25% of Al2O3, 15-25% of Na2O, 0-5% of K2O, 1-9% of Li2O, 0-4% of MgO, 0-4% of CaO, 1-15% of ZrO2, 0.5-5% of B2O3, 0.3-5% of P2O5, 3% of TiO2, 0.1-2% of a clarifying agent and 0.01-3% of an oxide pigment; the clarifying agent comprises at least one of SnO2, NaCl and Sb2O3. The nepheline dental microcrystalline glass is good in toughness, high in bending strength, high in hardness, good in wear resistance, good in chemical stability and good in biocompatibility, and can be applied to the field of high-performance dental materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of glass-ceramics, and in particular to sodium nepheline dental glass-ceramics, chemically strengthened sodium nepheline dental glass-ceramics, and preparation methods and applications thereof. Background Art

[0002] With the improvement of living standards, the number of people with dental health problems is gradually increasing. The aging population and the increase in accidents have also aggravated the phenomenon of broken and fallen teeth. People's demand for high-performance dental restoration materials is growing. Therefore, dentistry, especially the development of dental materials, has gradually become a major research hotspot.

[0003] Comparing the research on dentistry at home and abroad, it is found that domestic research is mostly focused on the adjustment and strengthening of the color of denture porcelain, and less attention is paid to the material itself, which is mostly controlled by foreign institutions. For example, the commercial lithium disilicate and white garnet dentures launched by Ivoire Company have better material performance and subsequent adjustment capabilities than domestic products. In terms of existing achievements, the main products on the market are Ivoire Company's IPS E.MAX Press and IPS E.MAX CAD products. Domestic research on lithium porcelain teeth is concentrated on the secondary research and development of lithium disilicate. Compared with imported denture products (bending strength of 360-450MPa), domestic products still have a large gap in mechanical properties. The main reason is that it is limited by the material. Compared with the mature lithium disilicate microcrystalline glass denture products abroad, the subsequent strength adjustment process is already quite mature and is in continuous iteration. The development of new materials is the fundamental solution to achieve overtaking on the curve.

[0004] Therefore, there is an urgent need to develop a dental glass-ceramic material with excellent mechanical properties. Summary of the invention

[0005] Based on the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide sodium nephrite dental glass-ceramics, chemically strengthened sodium nephrite dental glass-ceramics and their preparation methods and applications, aiming to provide sodium nephrite dental glass-ceramics with mechanical properties such as good toughness, high bending strength and high hardness.

[0006] The technical solution of the present invention is as follows:

[0007] In a first aspect of the present invention, a sodium nephrite dental glass-ceramics is provided, wherein, in terms of molar percentage, the sodium nephrite dental glass-ceramics comprises the following components:

[0008] SiO2 40%-55%, Al2O3 15%-25%, Na2O 15%-25%, K2O 0%-5%, Li2O1%-9%, MgO 0%-4%, CaO 0%-4%, ZrO2 1%-15%, B2O3 0.5%-5%, P2O5 0.3%-5%, TiO2 0%-3%, clarifier 0.1%-2% and oxide colorant 0.01%-3%;

[0009] The clarifier includes at least one of SnO2, NaCl and Sb2O3.

[0010] Optionally, the oxide colorant includes CeO2, V2O5, Tb4O7, Er2O3, Fe2O3, Eu2O3, Pr6O 11 , MnO2 and TiO2.

[0011] Optionally, the crystal phase of the sodium nepheline dental glass-ceramics includes a main crystal phase and a secondary crystal phase, the main crystal phase includes sodium nepheline, and the secondary crystal phase includes at least one of apatite, triclinic nepheline, ZrO2, nepheline solid solution, zirconia and β-quartz solid solution; the mass proportion of the main crystal phase is greater than 40% and less than 90%, and the grain size of the main crystal phase is 150-300nm.

[0012] A second aspect of the present invention provides a method for preparing the sodium nepheline dental glass-ceramics as described above, comprising the following steps:

[0013] Mixing ingredients according to the components of sodium nepheline dental glass-ceramics to obtain a mixed material;

[0014] After the mixture is melted, it is molded and annealed to obtain basic glass;

[0015] The base glass is subjected to nucleation treatment and crystallization treatment in sequence to obtain the sodium nephrite dental glass-ceramics.

[0016] Optionally, the melting temperature is 1400-1600° C., and the melting time is 2-5 hours.

[0017] Optionally, the temperature of the nucleation treatment is 450-580° C., and the time of the nucleation treatment is 180-600 min; the temperature of the crystallization treatment is 650-800° C., and the time of the crystallization treatment is 30-180 min.

[0018] Optionally, the forming method includes a float process, an overflow down-draw process, a roller pressing process or a casting process.

[0019] The third aspect of the present invention provides a chemically strengthened sodium nephrite dental glass-ceramics, wherein the chemically strengthened sodium nephrite dental glass-ceramics is prepared by ion exchange chemical strengthening of the sodium nephrite dental glass-ceramics as described above in the present invention and / or the sodium nephrite dental glass-ceramics prepared by the preparation method as described above in the present invention.

[0020] Optionally, the bending strength of the chemically strengthened sodium nepheline dental glass-ceramics is 270-450 MPa, and the fracture toughness of the chemically strengthened sodium nepheline dental glass-ceramics is not less than 1.5 MPa·m 0.5 .

[0021] A fourth aspect of the present invention provides a method for preparing chemically strengthened sodium nepheline dental glass-ceramics, which comprises the following steps:

[0022] The sodium nephrite dental glass-ceramics described above in the present invention and / or the sodium nephrite dental glass-ceramics prepared by the preparation method described above in the present invention are placed in molten salt for a preset time, and after ion exchange chemical strengthening, the chemically strengthened sodium nephrite dental glass-ceramics are obtained.

[0023] Optionally, the molten salt includes at least one of sodium nitrate, potassium nitrate, lithium nitrate, sodium chloride, potassium chloride, sodium sulfate and potassium sulfate.

[0024] The fifth aspect of the present invention provides a sodium nephrite dental glass-ceramic as described above, a sodium nephrite dental glass-ceramic prepared by the preparation method as described above, a chemically strengthened sodium nephrite dental glass-ceramic as described above, or a chemically strengthened sodium nephrite dental glass-ceramic prepared by the preparation method as described above in the field of dentistry.

[0025] Beneficial effects: The sodium nepheline dental glass-ceramics provided by the present invention has good toughness, is not easy to break, has high bending strength, high hardness, good wear resistance, good mechanical properties (or mechanical properties), chemical stability and biocompatibility, and can be applied to the field of high-performance dental materials. In addition, the glass-ceramics in the present invention has a low Li content and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 2 are XRD diagrams of the glasses in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0027] The present invention provides sodium nepheline dental glass-ceramics, chemically strengthened sodium nepheline dental glass-ceramics, and preparation methods and applications thereof. To make the purpose, technical scheme, and effects of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0028] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0029] The embodiment of the present invention provides a sodium nephrite dental glass-ceramic, wherein the sodium nephrite dental glass-ceramic includes the following components in terms of molar percentage:

[0030] SiO2 40%-55%, Al2O3 15%-25%, Na2O 15%-25%, K2O 0%-5%, Li2O1%-9%, MgO 0%-4%, CaO 0%-4%, ZrO2 1%-15%, B2O3 0.5%-5%, P2O5 0.3%-5%, TiO2 0%-3%, clarifier 0.1%-2% and oxide colorant 0.01%-3%; the clarifier comprises at least one of SnO2, NaCl and Sb2O3.

[0031] The sodium nepheline dental glass-ceramics provided in the embodiment of the present invention has good toughness, is not easy to break, has high bending strength, good wear resistance, and has good mechanical properties (or mechanical properties), chemical stability and biocompatibility, and can be applied to the field of high-performance dental materials (such as implant denture materials or crown modification materials, or dental materials for dental all-ceramic restoration). In addition, the glass-ceramics in the embodiment of the present invention has a low Li content and a low cost.

[0032] That is to say, different from the mature lithium disilicate system and zirconium oxide system, the sodium nepheline dental glass-ceramics provided in the embodiment of the present invention has good mechanical strength and biocompatibility, good toughness, and is not easy to break brittlely. It can be used as an implant denture or crown modification material, can meet the mechanical property requirements of teeth, and is used in practical applications such as dental restoration and dental implants.

[0033] In the present embodiment, the field strength and radius of the divalent metal ions in the sodium nephrite dental glass-ceramics component are higher than those of the monovalent ions, and they are aggregated on the surface of the glass after replacement, which is beneficial to the improvement of the surface chemical stability of the glass-ceramics. In this way, the chemical properties of the sodium nephrite dental glass-ceramics provided by the present invention are stable, can exist in the human body for a long time, and will not produce harmful substances. The rapid development of the lithium battery industry has led to an increase in the cost of lithium ore. The sodium nephrite dental glass-ceramics provided by the present invention has a low Li content and a low cost. Teeth include enamel, dentin, and cementum, including apatite crystals composed of calcium and phosphorus ions. The Ca and P in the sodium nephrite dental glass-ceramics provided by the present invention are not only essential elements for the human body, but also the main components of human bones and teeth. Therefore, the sodium nephrite dental glass-ceramics has good biocompatibility.

[0034] In this embodiment, SiO2, Na2O and Al2O3 are used as main raw materials, which are the basis for forming sodium nepheline and are mainly used to construct the main structure of the microcrystalline glass network.

[0035] SiO2, as the main network former, can stabilize the network structure, constitute the main structure of the precursor and sodium nepheline dental glass-ceramics, and is also the main component of some crystalline phases. In the present invention, the molar content of SiO2 is controlled to be 40% to 55% (for example, the molar content of SiO2 is 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55% or any value in the numerical range composed of any two of the above values ​​as endpoints), which can avoid the problems of smelting difficulties caused by too high content and the decrease in the overall mechanical properties of the glass-ceramics caused by too low content. More specifically, the molar content of SiO2 is 45% to 55%.

[0036] On the one hand, Al2O3 is an intermediate oxide in the formation of sodium nephrite dental glass-ceramics. On the other hand, it can increase the glass transition temperature and softening point, and improve the chemical stability of sodium nephrite dental glass-ceramics. Since [AlO4] has a larger spatial volume than [SiO4], it can provide a larger transport and replacement space for ion exchange, which promotes the ion exchange. Too high Al2O3 will increase the viscosity of the glass, which is not conducive to melting. Considering comprehensively, the molar content of Al2O3 is 15% to 25%, for example, the molar content of Al2O3 is 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value in the numerical range composed of any two of the above values ​​as endpoints.

[0037] Na2O is one of the main components of sodium nepheline and triclinic nepheline. It is also an important element for flux and ion exchange chemical strengthening to obtain sodium nepheline dental glass-ceramics. + Compared with the Na+ ions with small ionic radius in glass-ceramics + The exchange reaction can generate surface compressive stress on the surface of the sodium nephrite dental glass-ceramics, further improving the strength of the sodium nephrite dental glass-ceramics. In order to keep the melting temperature within a suitable range and ensure the subsequent chemical strengthening performance, the molar content of Na2O is 15% to 25%, for example, the molar content of Na2O is 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value in the numerical range consisting of any two of the above values ​​as endpoints.

[0038] K2O is an optional component for improving the low temperature melting property and formability of sodium nepheline dental glass-ceramics, but if the molar content of K2O is too high, it is easy to reduce the chemical stability of sodium nepheline dental glass-ceramics. Taking all factors into consideration, the molar content of K2O is 0% to 5%, for example, the molar content of K2O is 0%, 1%, 2%, 3%, 4%, 5%, or any value in a numerical range consisting of any two of the above values ​​as endpoints.

[0039] The main function of Li2O is to improve the chemical strengthening effect and reduce the high temperature viscosity of the glass. Its ion radius is smaller, which is conducive to diffusion and can increase the depth of the ion exchange layer in chemical strengthening. In order to obtain a good strengthening effect, the molar content of Li2O is 1% to 9% after comprehensive consideration, for example, the molar content of Li2O is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or any value in the numerical range composed of any two of the above values ​​as endpoints.

[0040] MgO can make the structure of sodium nephrite dental glass-ceramics more compact, has a certain fluxing effect, and can also improve chemical stability.

[0041] CaO, as a network exo-oxide formed by sodium nephrite dental glass-ceramics, helps to reduce the viscosity of sodium nephrite dental glass-ceramics, inhibits the crystallization of sodium nephrite dental glass-ceramics during the molding of sodium nephrite dental glass-ceramics, and can also improve the low-temperature melting property of sodium nephrite dental glass-ceramics. However, excessive CaO will reduce the devitrification resistance of sodium nephrite dental glass-ceramics. By adding an appropriate amount of CaO, the viscosity of sodium nephrite dental glass-ceramics can be reduced without affecting the crystallization performance of sodium nephrite dental glass-ceramics. Comprehensively considered, the molar content of CaO is 0% to 4%, for example, the molar content of CaO is 0%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or any value in the numerical range composed of any two of the above numerical values ​​as endpoints.

[0042] B2O3, as a network exometallic oxide of sodium nephrite dental glass-ceramics, is generally filled in the voids of the silicon-oxygen tetrahedral framework to form a low-eutectic glass network, which helps to improve the toughness of sodium nephrite dental glass-ceramics.

[0043] P2O5, TiO2 and ZrO2 can be used as nucleating agents to crystallize sodium nephrite dental glass-ceramics, among which P2O5 can promote the formation of crystals and improve biocompatibility. TiO2 can effectively promote the growth of crystal nuclei in the nucleation and crystallization process of the base glass, and at the same time improve the stability of the glass; the introduction of TiO2 can effectively promote the precipitation of crystal nuclei during the nucleation process, and at the same time, the introduction of TiO2 can easily cause the base glass to undergo phase separation, leading to crystallization and affecting the formation of the glass. ZrO2 also has the function of strengthening the glass network structure, and can enhance the strength of sodium nephrite dental glass-ceramics through phase change toughening, but excessive ZrO2 will significantly increase the viscosity of sodium nephrite dental glass-ceramics, making it difficult to melt and affecting the molding ability of sodium nephrite dental glass-ceramics. Taking all factors into consideration, the molar content of ZrO2 is 1% to 15%, for example, the molar content of ZrO2 is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value in the numerical range composed of any two of the above values ​​as endpoints; the molar content of P2O5 is 0.3% to 5%, for example, it can be 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5% or any value in the numerical range composed of any two of the above values ​​as endpoints; the molar content of TiO2 is 0% to 3%, for example, it can be 0%, 1%, 2%, 3% or any value in the numerical range composed of any two of the above values ​​as endpoints.

[0044] SnO2, NaCl, and Sb2O3 are good clarifiers in the production of sodium nepheline dental glass-ceramics, which can effectively homogenize the components of the precursor glass and reduce the formation of undesirable substances such as bubbles and stones. Taking all factors into consideration, the total molar content of one or more of SnO2, NaCl, and Sb2O3 is 0.1% to 2%, for example, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, or any value in the numerical range consisting of any two of the above values ​​as endpoints.

[0045] In some embodiments, the oxide colorant includes CeO2, V2O5, Tb4O7, Er2O3, Fe2O3, Eu2O3, Pr6O 11 At least one of CeO2, V2O5, Tb4O7, Er2O3, Fe2O3, Eu2O3, Pr6O 11 The molar content of at least one of MnO2 and TiO2 is 0.01% to 3%, for example, it can be 0.01%, 0.02%, 0.05%, 0.08%, 1%, 1.5%, 2%, 2.5%, 3% or any value in a numerical range consisting of any two of the above numerical values ​​as endpoints.

[0046] In some embodiments, the crystal phase of the sodium nepheline dental glass-ceramics includes a main crystal phase and a secondary crystal phase, the main crystal phase includes sodium nepheline, and the secondary crystal phase includes at least one of apatite, triclinic nepheline, ZrO2, nepheline solid solution, zirconium oxide and beta quartz solid solution; the mass proportion of the main crystal phase is greater than 40% and less than 90%, and the grain size of the main crystal phase is 150 to 300 nm. In this embodiment, by controlling the main crystal phase and the secondary crystal phase of the glass-ceramics, as well as the content and grain size of the main crystal phase, the sodium nepheline dental glass-ceramics obtains better toughness, higher bending strength and hardness.

[0047] The present invention also provides a method for preparing the sodium nephrite dental glass-ceramics according to the present invention, which comprises the following steps:

[0048] S1. Mixing ingredients according to the components of sodium nephrite dental glass-ceramics to obtain a mixture; wherein, in terms of molar percentage, the sodium nephrite dental glass-ceramics includes the following components:

[0049] SiO2 40%-55%, Al2O3 15%-25%, Na2O 15%-25%, K2O 0%-5%, Li2O1%-9%, MgO 0%-4%, CaO 0%-4%, ZrO2 1%-15%, B2O3 0.5%-5%, P2O5 0.3%-5%, TiO2 0%-3%, clarifier (specific selection see above) 0.1%-2% and oxide colorant (specific selection see above) 0.01%-3%.

[0050] S2, after the mixture is melted (the mixture is stirred 1 to 3 times during heating and melting), it is molded and annealed to obtain a basic glass;

[0051] S3, subjecting the base glass to nucleation treatment and crystallization treatment in sequence to obtain the sodium nephrite dental glass-ceramics.

[0052] The preparation method provided by the present invention is simple, and the prepared sodium nepheline dental glass-ceramics have excellent mechanical properties (good toughness, not easy to break, high mechanical strength), chemical stability (can exist in the human body for a long time, will not produce harmful substances) and good biocompatibility, and can be applied to the field of high-performance dental materials (such as dental all-ceramic restoration materials, implant dentures or crown modification materials). In addition, the glass-ceramics in the invention have a low Li content and low cost.

[0053] In step S2, in some embodiments, the melting temperature is 1400-1600°C (for example, it can be 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, or any value in a numerical range consisting of any two of the above values ​​as endpoints), and the melting time is 2-5h (for example, it can be 2h, 3h, 4h, 5h, or any value in a numerical range consisting of any two of the above values ​​as endpoints).

[0054] In some embodiments, the forming method comprises a float process, an overflow down-draw process, a roller pressing process or a casting process.

[0055] In some embodiments, the annealing temperature is 420-600°C (for example, it can be 420°C, 450°C, 500°C, 550°C, 600°C, or any value in a numerical range consisting of any two of the above values ​​as endpoints), and the annealing time is 180-600 min (for example, it can be 180 min, 200 min, 250 min, 300 min, 350 min, 400 min, 450 min, 500 min, 550 min, 600 min, or any value in a numerical range consisting of any two of the above values ​​as endpoints).

[0056] In step S3, in some embodiments, the temperature of the nucleation treatment is 450-580°C (for example, 450°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C or any value in a numerical range consisting of any two of the above values ​​as endpoints), and the time of the nucleation treatment is 180-600min (for example, 180min, 200min, 250min, 300min, 350min, 400min, 450min, 500min, 550min, 600min or any value in a numerical range consisting of any two of the above values ​​as endpoints). Further, the temperature of the nucleation treatment is 480-550°C, and the time of the nucleation treatment is 240-600min.

[0057] In some embodiments, the temperature of the crystallization treatment is 650-800°C (for example, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, or any value in a numerical range consisting of any two of the above values ​​as endpoints), and the time of the crystallization treatment is 30-180 min (for example, 30 min, 50 min, 100 min, 120 min, 150 min, 160 min, 180 min, or any value in a numerical range consisting of any two of the above values ​​as endpoints). Further, the temperature of the crystallization treatment is 680-780°C, and the time of the crystallization treatment is 30-120 min.

[0058] An embodiment of the present invention also provides a chemically strengthened sodium nepheline dental glass-ceramics, wherein the chemically strengthened sodium nepheline dental glass-ceramics is prepared by ion exchange chemical strengthening of the sodium nepheline dental glass-ceramics as described above in the embodiment of the present invention and / or the sodium nepheline dental glass-ceramics prepared by the preparation method as described above in the embodiment of the present invention.

[0059] The chemically strengthened sodium nepheline dental glass-ceramics provided by the embodiment of the present invention has a surface Vickers hardness of 500-800 HV, a bending strength of 200-450 MPa, and a fracture toughness of not less than 1.5 MPa·m 0.5 , more specifically, the fracture toughness is 1.5 to 3 MPa·m 1 / 2 The chemically strengthened sodium nepheline dental glass-ceramics has good toughness, is not easy to break, has excellent mechanical properties, chemical stability and good biocompatibility, and can be applied to the field of high-performance dental materials (such as dental all-ceramic restoration materials, implant denture materials or crown modification materials).

[0060] The embodiment of the present invention also provides a method for preparing chemically strengthened sodium nepheline dental glass-ceramics, which comprises the following steps:

[0061] The sodium nephrite dental glass-ceramics as described above in the embodiment of the present invention and / or the sodium nephrite dental glass-ceramics prepared by the preparation method as described above in the embodiment of the present invention are placed in molten salt for a preset time, and after ion exchange chemical strengthening, the chemically strengthened sodium nephrite dental glass-ceramics are obtained.

[0062] In some embodiments, the molten salt includes at least one of sodium ions, lithium ions, and potassium ions, the temperature of the molten salt is 350-500°C (for example, it can be 350°C, 380°C, 400°C, 420°C, 450°C, 480°C, 500°C, or any value in a numerical range composed of any two of the above values ​​as endpoints), and the preset time is 1-36h (for example, it can be 1h, 2h, 5h, 8h, 10h, 15h, 20h, 25h, 30h, 35h, 36h, or any value in a numerical range composed of any two of the above values ​​as endpoints).

[0063] In some embodiments, the molten salt includes at least one of sodium nitrate, potassium nitrate, lithium nitrate, sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate, but is not limited thereto.

[0064] An embodiment of the present invention also provides a sodium nephrite dental glass-ceramic as described above in the embodiment of the present invention, a sodium nephrite dental glass-ceramic prepared by the preparation method described above in the embodiment of the present invention, a chemically strengthened sodium nephrite dental glass-ceramic as described above in the embodiment of the present invention, or a chemically strengthened sodium nephrite dental glass-ceramic prepared by the preparation method described above in the embodiment of the present invention, and their use in the field of dentistry (such as as implant denture material, crown modification material or dental all-ceramic restoration material).

[0065] The present invention will be further described below by means of specific examples.

[0066] Table 1. Formula of glass in various embodiments and comparative examples

[0067]

[0068]

[0069] Example 1

[0070] This embodiment provides a method for preparing chemically strengthened sodium nepheline dental glass-ceramics, comprising the following steps:

[0071] (1) According to the components and proportions of Example 1 in Table 1, weigh the raw materials and mix them to obtain a mixture:

[0072] (2) The mixture is placed in a platinum crucible, heated to 1500°C, and kept warm for 4 hours. The molten liquid needs to be stirred twice during the warming process.

[0073] (3) The molten liquid obtained in the above step (2) is cast into a preheated mold, and subjected to annealing treatment (temperature of 450° C., time of 360 min) to obtain a basic glass.

[0074] (4) The base glass is placed in a resistance furnace and kept at 500°C for 240 minutes for nucleation treatment; then kept at 700°C for 120 minutes for crystallization treatment, and after CAD / CAM (CAD is computer-aided design, CAM is computer-aided manufacturing) dental processing technology, sodium nepheline dental microcrystalline glass is obtained.

[0075] (5) The sodium nepheline dental glass-ceramics obtained in the above step (4) is placed in a molten salt (99wt% NaNO3+1wt% KNO3) at 400°C for chemical strengthening for 600 minutes to obtain chemically strengthened sodium nepheline dental glass-ceramics (also known as strengthened dental glass-ceramics).

[0076] Example 2

[0077] This embodiment provides a method for preparing chemically strengthened sodium nepheline dental glass-ceramics, which is different from the embodiment 1 only in that:

[0078] In step (1), weigh the raw materials according to the components and proportions of Example 2 in Table 1;

[0079] In step (2), heating to 1550° C. and keeping the temperature for 3 h;

[0080] In step (3), the annealing temperature is 450°C and the time is 400 min;

[0081] In step (4), the base glass is placed in a resistance furnace and kept at 550° C. for 300 minutes for nucleation treatment; and then kept at 700° C. for 120 minutes for crystallization treatment;

[0082] In step (5), the sodium nepheline dental glass-ceramics obtained in the above step (4) is placed in a molten salt (99wt% NaNO3+1wt% KNO3) at 480°C for chemical strengthening for 600 minutes to obtain chemically strengthened sodium nepheline dental glass-ceramics.

[0083] Example 3

[0084] This embodiment provides a method for preparing chemically strengthened sodium nepheline dental glass-ceramics, which is different from the embodiment 1 only in that:

[0085] In step (1), weigh the raw materials according to the components and proportions of Example 3 in Table 1;

[0086] In step (2), heating to 1550° C. and keeping the temperature for 4 h;

[0087] In step (3), the annealing temperature is 550° C. and the time is 400 min;

[0088] In step (4), the base glass is placed in a resistance furnace and kept at 550° C. for 300 minutes for nucleation treatment; and then kept at 665° C. for 40 minutes for crystallization treatment;

[0089] In step (5), the sodium nepheline dental glass-ceramics obtained in the above step (4) is placed in a molten salt (99wt% NaNO3+1wt% KNO3) at 480°C for chemical strengthening for 600 minutes to obtain chemically strengthened sodium nepheline dental glass-ceramics.

[0090] Example 4

[0091] This embodiment provides a method for preparing chemically strengthened sodium nepheline dental glass-ceramics, which is different from the embodiment 1 only in that:

[0092] In step (1), weigh the raw materials according to the components and proportions of Example 4 in Table 1;

[0093] In step (2), heating to 1500° C. and keeping the temperature for 4 h;

[0094] In step (3), the annealing temperature is 550°C and the time is 360 min;

[0095] In step (4), the base glass is placed in a resistance furnace and kept at 550° C. for 300 minutes for nucleation treatment; and then kept at 700° C. for 150 minutes for crystallization treatment;

[0096] In step (5), the sodium nepheline dental glass-ceramics obtained in the above step (4) is placed in a molten salt (99wt% NaNO3+1wt% KNO3) at 480°C for chemical strengthening for 600 minutes to obtain chemically strengthened sodium nepheline dental glass-ceramics.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing a chemically strengthened glass-ceramics, which differs from Example 1 only in that:

[0099] In step (1), weigh the raw materials according to the components and proportions of Comparative Example 1 in Table 1;

[0100] In step (2), heating to 1550° C. and keeping the temperature for 3 h;

[0101] In step (3), the annealing temperature is 450°C and the time is 400 min;

[0102] In step (4), the base glass is placed in a resistance furnace and kept at 550° C. for 300 minutes for nucleation treatment; and then kept at 700° C. for 60 minutes for crystallization treatment;

[0103] In step (5), the microcrystalline glass obtained in the above step (4) is placed in a molten salt (99wt% NaNO3+1wt% KNO3) at 500°C for chemical strengthening for 600 minutes to obtain chemically strengthened microcrystalline glass.

[0104] Comparative Example 2

[0105] This comparative example provides a method for preparing a chemically strengthened glass-ceramics, which differs from Example 1 only in that:

[0106] In step (1), weigh the raw materials according to the components and proportions of Comparative Example 2 in Table 1;

[0107] In step (2), heating to 1550° C. and keeping the temperature for 3 h;

[0108] In step (3), the annealing temperature is 450°C and the time is 400 min;

[0109] In step (4), the base glass is placed in a resistance furnace and kept at 550° C. for 300 minutes for nucleation treatment; and then kept at 700° C. for 120 minutes for crystallization treatment;

[0110] In step (5), the microcrystalline glass obtained in the above step (4) is placed in a molten salt (99wt% NaNO3+1wt% KNO3) at 480°C for chemical strengthening for 600 minutes to obtain chemically strengthened microcrystalline glass.

[0111] The glasses in the embodiments and comparative examples were tested:

[0112] (1) Crystal phase and its content, main crystal phase testing;

[0113] The glass-ceramics were ground into powder, and the crystal phase composition of the transparent glass-ceramics was analyzed by Rigaku Smartlab X-ray diffraction (XRD) test. Jade was used to analyze the crystal phase composition (types of primary and secondary crystal phases), the proportion of each crystal phase, and the crystal size.

[0114] (2) L value, a value and b value test;

[0115] Lab is a color model based on physiological characteristics, where L represents brightness, a includes colors from dark green to gray to bright pink, and b includes colors from bright blue to gray to yellow. The b value in Lab can represent the deviation of an object between yellow and blue. Tested by Konica Minolta Spectrophotometer CM-3600A.

[0116] (3) Bending strength test:

[0117] The glass samples to be tested were prepared into sheets (30mm×4mm×3mm) using low-speed cutting equipment and grinding equipment and surface polished with iron oxide, and then the glass samples were subjected to bending strength tests using a universal strength tester using a three-point bending test method. The instrument loading speed is 1mm / min, the span is 20mm, and the maximum load can be obtained when the glass is broken. The bending strength of the glass sample can be calculated using the formula, which is as follows:

[0118]

[0119] Among them, M is the three-point bending strength (MPa), W is the maximum load (N), l is the span (mm), b is the sample width (mm), and d is the sample thickness (mm). The bending strength of the glass sample can be obtained through calculation.

[0120] (4) Vickers hardness test:

[0121] Use a digital microhardness tester to test, and each group of glass samples has no less than 5 test points. The test pressure is 1kg, and the pressure is maintained for 10s. The hardness HV of the glass sample is calculated based on the size of the indentation caused by the indenter on the glass sample (load is 1kg). The formula is as follows:

[0122]

[0123] Where HV is the Vickers hardness value, F is the applied pressure, and d 2 is the indentation area.

[0124] (5) Fracture toughness test:

[0125] The fracture toughness of glass samples is measured using the indentation method. Each group of glass samples has no less than 5 test points and the test pressure is 1kg. The pressure is maintained for 10 seconds. The calculation formula is as follows:

[0126]

[0127] Where KIC is the fracture toughness, unit is MPa·m 1 / 2 ; E is Young's modulus, in GPa. P is load, in N; C is crack length, in mm; HV is Vickers hardness, in GPa.

[0128] (6) Biocompatibility testing

[0129] Prepare a cell culture dish, put in 10mL of periodontal ligament stem cells, and add the dental microcrystalline glass material in each embodiment and comparative example to the cell culture system. Set up a blank control group (not containing dental microcrystalline glass material). Culture cells at 35°C and 90% relative humidity for 24 hours, use the MTT method to detect cell viability, add MTT solution, absorb the culture solution in the well, add 5mg / mL of MTT solution to each well, continue to culture for 5 hours, and after the incubation is over, carefully absorb the MTT solution in the well, add an appropriate amount of DMSO (dimethyl sulfoxide) to each well, and shake gently to fully dissolve the purple crystals; measure the absorbance, and use an enzyme marker to measure the absorbance value of each well at a specific wavelength of 490nm. Calculate cell viability based on the absorbance value and calculate the relative cell survival rate.

[0130] The test results are shown in Table 2.

[0131] Table 2. Test results of various embodiments and comparative examples

[0132]

[0133]

[0134] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A sodium nepheline dental glass-ceramic, characterized in that: The sodium nepheline dental glass-ceramics comprises the following components in terms of molar percentage: SiO2 40%-55%, Al2O3 15%-25%, Na2O 15%-25%, K2O 0%-5%, Li2O1%-9%, MgO 0%-4%, CaO 0%-4%, ZrO2 1%-15%, B2O3 0.5%-5%, P2O5 0.3%-5%, TiO2 0%-3%, clarifier 0.1%-2% and oxide colorant 0.01%-3%; the clarifier comprises at least one of SnO2, NaCl and Sb2O3.

2. The sodium nepheline dental glass-ceramics according to claim 1, characterized in that: The oxide colorant includes CeO2, V2O5, Tb4O7, Er2O3, Fe2O3, Eu2O3, Pr6O 11 , MnO2 and TiO2.

3. The sodium nepheline dental glass-ceramics according to claim 1, characterized in that: The crystal phase of the sodium nepheline dental glass-ceramics includes a main crystal phase and a secondary crystal phase, the main crystal phase includes sodium nepheline, and the secondary crystal phase includes at least one of apatite, triclinic nepheline, ZrO2, nepheline solid solution, zirconia and β-quartz solid solution; the mass proportion of the main crystal phase is greater than 40% and less than 90%, and the grain size of the main crystal phase is 150 to 300 nm.

4. A method for preparing the sodium nepheline dental glass-ceramics according to claim 1, characterized in that: The steps include: Mixing ingredients according to the components of sodium nepheline dental glass-ceramics to obtain a mixed material; After the mixture is melted, it is molded and annealed to obtain basic glass; The base glass is subjected to nucleation treatment and crystallization treatment in sequence to obtain the sodium nephrite dental glass-ceramics.

5. The preparation method according to claim 4, characterized in that: The melting temperature is 1400-1600° C., and the melting time is 2-5 hours.

6. The preparation method according to claim 4, characterized in that: The temperature of the nucleation treatment is 450-580° C., and the time of the nucleation treatment is 180-600 min; the temperature of the crystallization treatment is 650-800° C., and the time of the crystallization treatment is 30-180 min.

7. The preparation method according to claim 4, characterized in that: The forming method includes a float process, an overflow down-draw process, a roller pressing process or a casting process.

8. A chemically strengthened sodium nepheline dental glass-ceramics, characterized in that: The chemically strengthened sodium nepheline dental glass-ceramics are prepared by subjecting the sodium nepheline dental glass-ceramics described in any one of claims 1 to 3 and / or the sodium nepheline dental glass-ceramics prepared by the preparation method described in any one of claims 4 to 7 to ion exchange chemical strengthening.

9. The chemically strengthened sodium nepheline dental glass-ceramics according to claim 8, characterized in that: The bending strength of the chemically strengthened sodium nepheline dental glass-ceramics is 270-450 MPa, and the fracture toughness of the chemically strengthened sodium nepheline dental glass-ceramics is not less than 1.5 MPa·m 0.5 .

10. A method for preparing chemically strengthened sodium nepheline dental glass-ceramics, characterized in that: The steps include: The sodium nephrite dental glass-ceramics described in any one of claims 1 to 3 and / or the sodium nephrite dental glass-ceramics prepared by the preparation method described in any one of claims 4 to 7 are placed in a molten salt for a preset time, and after ion exchange chemical strengthening, the chemically strengthened sodium nephrite dental glass-ceramics are obtained.

11. The preparation method according to claim 10, characterized in that: The molten salt includes at least one of sodium nitrate, potassium nitrate, lithium nitrate, sodium chloride, potassium chloride, sodium sulfate and potassium sulfate.

12. Use of the sodium nephrite dental glass-ceramic as described in any one of claims 1-3, the sodium nephrite dental glass-ceramic prepared by the preparation method described in any one of claims 4-7, the chemically strengthened sodium nephrite dental glass-ceramic as described in any one of claims 8-9, or the chemically strengthened sodium nephrite dental glass-ceramic prepared by the preparation method described in any one of claims 10-11 in the field of dentistry.